PGLYRP1-mediated intracellular peptidoglycan detection promotes intestinal mucosal protection - Shuyuan Chen; Rachel Putnik; Xi Li; Alka Diwaker; Marina Vasconcelos; Shuzhen Liu; Sudershan Gondi; Junhui Zhou; Lei Guo; Lin Xu; Sebastian Temme; Klare Bersch; et al. (Nature Communications, 2025)
Abstract Peptidoglycan recognition proteins (PGLYRPs) are implicated in the control of the intestinal microbiota; however, molecular requirements for peptidoglycan (PGN) binding and receptor signaling mechanisms remain poorly understood. Here we show that PGLYRP1 is a receptor for the disaccharide motif of lysine N-acetylglucosamine N-acetylmuramic tripeptide (GMTriP-K). PGLYRP1 is required for innate immune activation by GMTriP-K but not muramyl dipeptide (MDP). In macrophages, intracellular PGLYRP1 complexes with NOD2 and GEF-H1, both of which are required for GMTriP-K-regulated gene expression. PGLYRP1 localizes to the endoplasmic reticulum and interacts at the Golgi with NOD2 upon GMTriP-K stimulation. PGLYRP1 and dependent gene expression signatures are induced in both mouse intestinal inflammation and human ulcerative colitis. Importantly, PGLYRP1 activation by GMTriP-K can result in the protection of mice from TNBS-induced colitis. Mammalian PGLYRPs can function as intracellular pattern recognition receptors for the control of host defense responses in the intestine.